High-velocity H2O maser emission from the post-asymptotic-giant-branch star OH 009.1–0.4 - Walsh, Andrew; Breen, S.; Bains, I.; Vlemmings, W. (Wiley-Blackwell Publishing Ltd., 2009)
Observations of H2O masers towards the post-asymptotic-giant-branch star and water fountain source OH 009.1-0.4 were made as part of The H2O southern galactic Plane Survey, with the Mopra radiotelescope. Together with followup observations using the Australia Telescope Compact Array (ATCA), we have identified H2O maser emission over a velocity spread of nearly 400 kms-1 (-109to +289kms-1). This velocity spread appears to be the largest of any known maser source in our Galaxy. High-resolution observations with the ATCA indicate that the maser emission is confined to a region 0.3 × 0.3 arcsec and shows weak evidence for a separation of the red- and blueshifted maser spots. We are unable to determine if the water fountain is projected along the line of sight, or is inclined, but either way OH 009.1-0.4 is an interesting source, worthy of followup observations.